Asas Ketertiban Umum dalam Pelaksanaan Putusan Arbitrase Internasional di Indonesia - A.A. Istri Agung Cintya Anomsari; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Warmadewa Press, 2025)
Settlement of international business disputes is usually resolved through international arbitration, as it is